PENGGUNAAN MEDIA PEMBELAJARAN MENUJU PRODUKTIVITAS BELAJAR PESERTA DIDIK - Midun, Hendrikus (STKIP Santu Paulus Ruteng, 2016)
Abstract: Using Instructional Media Toward Learners’ Learning Productivity. One of the educational responses to changes in the world, specifically changes in information and communication technology, is the imperative employment of media in learning. One form of the imperative application is the use of media as a learning strategy. As a learning strategy, planning and using instructional media which are made consciously and systematically lead to the quality of learning such as managing the learners’ potentialities through optimum involvement in learning enterprises. Thus, the application of media has shifted learning paradigm from transfering knowledge to learning efforts. Consequently, learning efforst brings an impact on the choice and use of instructional methods. Lecturing method is replaced by with project method, discussion, presentation, portfolio, demonstration, and still many other types of cooperative learning methods which enable learners to keep the continuity of learning activities. Keywords: learning media, productivity learning, learners Abstrak: Penggunaan Media Pembelajaran Menuju Produktivitas Belajar Peserta Didik. Salah satu respon pendidikan terhadap perubahan dunia, khusus perubahan bidang teknologi informasi dan komunikasi adalah imperatif penggunaan media dalam pembelajaran. Salah satu bentuk aplikasi dari imperatif tersebut adalah penggunaan media sebagai strategi pembelajaran. Sebagai strategi pembelajaran, perencanaan dan penggunaan media pembelajaran dibuat secara sadar dan sistematis. Perencanaan dan penggunaan media secara sadar dan sistematis berorientasi pada mutu pembelajaran yang tampak pada optimalisasi pemberdayaan potensi-potensi belajar peserta didik melalui pelibatan yang optimal dalam berbagai aktivitas pembelajaran. Dengan demikian, penggunaan media pembelajaran merubah paradigma pembelajaran dari transfer pengetahuan dari pendidik kepada peserta didik menjadi upaya membelajarkan peserta didik. Upaya membelajarkan peserta didik berdampak pada perubahan pilihan dan penggunaan metode pembelajaran. Metode ceramah dirubah dan disempurnakan dengan metode penugasan, diskusi, laporan tugas, portofolio, demonstrasi, dan beragam jenis kooperatif learning sehingga memungkinkan peserta didik melakukan aktivitas belajar terus menerus. Kata kunci: media pembelajaran, produktivitas belajar, peserta didik